Program Open Ship Day Sebagai Kegiatan Sosialisasi Pengawasan Sumber Daya Kelautan Perikanan (PSDKP) Kalimantan Barat - Warsidah; Safitri, Ikha; Sofiana, Mega Sari Juane; Kushadiwijayanto , Arie Antasari; Nurrahman , Yusuf Arief; Helena, Shifa; Nurdiansyah , Syarif Irwan; Edwin (Jurnal Pengabdian kepada Masyarakat Nusantara, 2023)
Indonesia has very high marine fisheries resources so it is often the target of illegal fishing, both by local Indonesian fishermen who do not have permits to use special fishing gear and by foreign fishermen who enter Indonesian territorial waters. The Marine Fisheries Resources Monitoring Station (PSDKP) is the spearhead of monitoring and controlling the management of marine fisheries resources in Indonesian waters. The aim of this activity is to obtain information about the monitoring mechanism for marine fisheries resources in Indonesian waters, especially for WPP711 which covers the operational areas of the Natuna Sea, North Natuna Sea and Karimata Strait through Open Ship Day activities. The scope of PSDKP activities is from upstream to downstream processes, from monitoring and controlling fishing regulations to the monitoring and controlling of fish cultivation regulations and fishery product processing. The activity was attended by 20 participants consisting of students from the Marine Science Study Program at Tanjungpura University. The activity was carried out using the educational lecture method and a simulation of the mechanism for catching fishing vessels carrying out illegal fishing by the ABK Hiu Macan 01 team. The evaluation results showed that the participants in this activity had a good understanding of the mechanism for monitoring and controlling the use of fisheries marine resources in the WPP711 zone and got an overview of mechanism for encircling and arresting foreign fishing vessels that carry out illegal fishing.